The Distribution of Good Character Components in the Education System in the Society 5.0 Era - Zulkifli Musthan; M. Daud Yahya; Amie Primarni; Mamik Slamet; Muhammad Aufal Minan (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
There are three (3) backgrounds making this research urgent, namely first the complexity of character education challenges in the society 5.0 era. Second, in the Society 5.0 era, a strategic character education strategy is essential. Third, good character distribution in the education system is able to become a character education strategy in the society 5.0 era. This research is library research aiming to analyze descriptive research. The research finding shows that character education in the education system in the society 5.0 era is a conscious and planned effort to make humans have morals and ethics in personal, social, and national life. Character education implementation in the education system must consider good character component distribution. Good character components are generally classified into three (3) aspects, namely knowledge of character (moral knowing), habits of character (moral feeling), and character-driven action (moral action). Good character values have become urgent to be developed in the society 5.0 era, referring to good character values in the distribution era. The good character values formula, totaling eighteen (18) character values as contained in the National Education System Law Number 20 of 2003, can certainly become the main reference for developing good character values. In general, there are two (2) models of good character distribution in the education system in the society 5.0 era, namely the substantive and reflective models. The term assessment is synonymous with the term evaluation, which includes activities such as gathering, analyzing, and interpreting data about students' processes and learning outcomes that are carried out systematically and continuously to serve as meaningful information data, which is then followed up on.